Patterns of C-reactive protein trends during clozapine titration and the onset of clozapine-induced inflammation: a case series of weekly and daily C-reactive protein monitoring - Kikuchi, Yuki; Tanifuji, Hiroaki; Ueno, Sota; Onuma, Yoshifumi; Goto, Masatomo; Ishihara, Masato; Toraiwa, Takeshi; Komatsu, Hiroshi; Tomita, Hiroaki (Frontiers in Psychiatry, 2024)
Background: International guidelines for clozapine titration recommend measuring C-reactive protein (CRP) weekly for 4 weeks after clozapine initiation to prevent fatal inflammatory adverse events, including myocarditis. However, limited evidence exists regarding whether weekly CRP monitoring can prevent clozapine-induced inflammation.We examined the relationship between CRP trends and the development of clozapine-induced inflammation. We also explored the usefulness and limitations of CRP monitoring during clozapine titration.Method: This study presents 17 and 4 cases of weekly and daily CRP monitoring during clozapine initiation, respectively.Results: Among 17 patients with weekly CRP measurements, 7 had fever. Elevated CRP levels were detected before the onset of fever in two of the seven patients. Of the five remaining patients, the CRP levels on a previous test had been low; however, the fever developed suddenly. Of the 10 patients with no fever under weekly CRP monitoring, three had elevated CRP levels >3.0 mg/dL. Refraining from increasing the clozapine dose may have prevented fever in these patients. Among four patients with daily CRP measurements, two became febrile. In both cases, CRP levels increased almost simultaneously with the onset of fever.Weekly and daily CRP monitoring during clozapine titration is valuable for preventing clozapine-induced inflammation, assessing its severity, and guiding clozapine dose adjustments. Weekly CRP monitoring may not adequately predict clozapine-induced inflammation in some cases. Consequently, clinicians should be aware of the sudden onset of clozapine-induced inflammation, even if CRP levels are low. Daily CRP monitoring is better for detecting clozapine-induced inflammation.